Tick host specificity: an analysis based on host phylogeny and tick ecological features using Amblyomma triste and Amblyomma tigrinum immature stages - Colombo, Valeria Carolina; Fasano, Agustín Alfonso; Beldomenico, Pablo Martín; Nava, Santiago (2018)
Here we have evaluated tick host specificity with two different methodological approaches considering Amblyomma tigrinum and Amblyomma triste immatures as targets. Firstly, the Std* index was applied, which considers host phylogenetic relationships weighted by the prevalence of the parasite; followed by generalized linear models to explore associations between different host species and burdens and prevalence of larvae and nymphs, independently. The Std* index showed that A. tigrinum larvae and nymphs infest host species belonging to different orders and classes, respectively; while A. triste immatures fed on hosts that belong to different tribes, showing that both tick species have low specificity and thus, a generalist behavior. When analyzing prevalence and burdens, we found that both tick species infest some hosts more heavily compared with the rest. Even though immature stages of A. triste and A. tigrinum are generalists, the level of infestation within the range of usual hosts of these two species is uneven. This shows that a generalist behavior may result in dissimilar levels of infestation across a range of usual hosts.